REUSE OF SILICON POWDER ARISING OUT OF PRODUCTION OF SEMICONDUCTORS IN THE CONSTRUCTION INDUSTRY - BREJÃO, Antonio S; MORAIS, Marcos de O.; VENDRAMETTO, Oduvaldo (Revista Brasileira de Engenharia de Biossistemas, 2013)
For the semiconductor industry, the residue of silicon powder is a problem in the field of industrial ecology. The purpose of this paper is to analyze the characteristics of this waste, aiming to close the production cycle. Silicon powder obtained through the cutting process of the silicon wafers was characterized by physical tests and optical microscopy. After separation, the residue was added to the cement forming joint specimens and therefore, we assessed the possible gain in compressive strength compared to ordinary cement, proving the technical feasibility of using this type of waste in the manufacture of cement products.